Atrial fibrillation incidence and risk factors in relation to race-ethnicity and the population attributable fraction of atrial fibrillation risk factors: the Multi-Ethnic Study of Atherosclerosis - Rodriguez, Carlos J.; Soliman, Elsayed Z.; Alonso, Alvaro; Swett, Katrina; Okin, Peter M.; Goff, David C.; Heckbert, Susan R. (Annals of epidemiology, 2015)
We studied incident atrial fibrillation (AF) in the prospective community-based Multi-Ethnic Study of Atherosclerosis (MESA). Reportedly, non-Hispanic blacks (NHBs) have a lower AF burden compared with their non-Hispanic white (NHW) counterparts. Information on the epidemiology of AF in Hispanic and Asian populations is much more limited. We excluded participants with a history of AF at enrollment. A total of 6721 MESA participants were monitored for the first AF event ascertained according to hospital discharge International Classification of Diseases, Ninth Revision, codes. Age- and sex-adjusted incidence rates (IRs) of AF were calculated per 1000 person-years of observation. IR ratios were calculated using NHWs as the reference group. Age- and sex-adjusted population attributable fractions (PAFs) of established modifiable AF risk factors were ascertained. In the MESA cohort, 47.2% was male; at baseline, 25.7% had hypertension; 12.5% had diabetes. Three hundred five incident hospitalized AF events occurred over a mean follow-up of 7.3 years. Age- and sex-adjusted IRs and IR ratios showed that overall AF incidence was significantly lower among Hispanics, NHBs and Chinese compared with NHWs (all P < .001). Among participants 65 years of age or greater, Hispanics, Chinese, and blacks had significantly lower AF incidence than NHWs (all P ≤ .01), but IRs were similar among participants under age 65 years. The PAF for smoking was 27% among NHBs but lower among other race–ethnic groups. Among NHWs, the PAF for hypertension was 22.2%, but this was higher among NHBs (33.1%), Chinese (46.3%), and Hispanics (43.9%). Overall, the incidence of hospitalized AF was significantly lower in Hispanics, NHBs, and Chinese than in NHWs. A larger proportion of AF events appear to be attributable to hypertension among nonwhite populations compared with NHWs.